The House of European History: Pöttering’s Elite-Level Impact in shaping European Identity - Ostojski, Jennifer (Politologija, 2023)
The House of European History in Brussels, Belgium, is a pan-European identity-making institution, created by the European Union. It has sparked an array of scholarship that speaks to the power of the museum, its ability to create a master narrative for the European people, and the varying omissions and choices made in telling Europe’s history. While European Parliament President Hans-Gert Pöttering receives credit for originating the museum, little scholarship speaks to his ideas regarding European Union integration, community, and its identity – even though, elite leader ideas are recognized in nationalism studies as instrumental in the making of an identity. This article fills this gap and shows how Pöttering’s ideas influenced the broad and generalized narrative the House of European History espouses today.
Keywords: House of European History; European Union; European Integration; European Identity; Hans-Gert Pöttering